Housing Affordability Factors for Urban Liveability - A Preliminary Study - Abdul Shakur, Elia Syarafina; Mohamed, Ahmad Fariz; Abdul Hadi, Abdul Samad (International Journal of Property Sciences (E-ISSN: 2229-8568), 2017)
Affordability and homeownership are important factors of urban livability. However, given the rapid increase in house prices and the slower growth of individual incomes in Malaysia, the ability to own a house presents a significant challenge. Rising costs of living add to the problem. Current trends show that housing unaffordability is particularly acute among the middle-income earners, the group that constitutes the main bulk of the Malaysian urban populace. Housing affordability impinges upon urban livability. This paper reports a study that was undertaken to analyse specific factors (namely location, demand, construction costs and service costs) regarding their effects on house prices and housing affordability of the middle-income group. The town of Kajang (Selangor, Malaysia) was chosen as the case study area while the focus is centred on the two most popular segments of residential properties, the single- and double-storey terraced houses. The purpose of this study is to analyse how affordability affects home ownership and to determine its effect towards urban livability. Key findings from this study concluded that there is a link between income and affordability, rapid house price increase affect home ownership and the livability of the middle-income group in the cities in Malaysian.